Physiology, biometry and mineral nutrition of cocoa clones cultivated in full sun - Benjamin, Carolina Santos (2021)
The cultivation of cocoa in full sun seeks technological modernization and yield increase; however, very little is known about this new production model. Thus, the aim of the present study was to: i) characterize six cocoa clones (PS 1319, CCN 51, CCN 10, SJ 02, CP 49 and PH 16), grown in full sun in Linhares, in the north of the state of Espírito Santo, regarding their physiology, leaf structure, yield and biometrics of fruits and seeds; ii) establishment of a nutritional sufficiency range through a leaf analysis and nutrient exportation of these six cocoa clones. The physiological evaluation and of the leaf structure took place by means of measurements of gas exchanges, chlorophyll flourescence, concentration of chloropastidic pigments, specific leaf area (SLA), stomatal density (SD) and potential quantum yield of photosystem II - Fv/Fm ratio. Yield was estimated by counting and weighing healthy seeds and fruits. For the biometrics of fruits and seeds, the following were evaluated: weight (LW); fruit length (FL) and diameter (FD), fresh weight of the shell (FWS), wet weight of the seed (WWA), number of seeds (NS) and individual weight of dry seed (IWDS). For the leaf sampling, four plants of each clone were randomly chosen, from which four diagnostic leaves were collected per plant. As for the fruit sampling, 10 ripe and healthy fruits were collected per clone and the separation of the shell and almonds was carried out. After the preparation of the leaf and fruit samples, they were sent to the laboratory for the quantification of the contents of mineral nutrients. The evaluation of almond yield was performed during the main and intercrop seasons and, for each clone, the healthy fruits and their seeds were collected, counted and weighed. After checking the high yield of the clones and the data normal distribution, the adequate sufficiency ranges were established considering μ ± σ. The trial was analyzed as a hierarchy classification, and for each one of the six clones, 14 plots were randomly plotted, each one composed of 1 plant (experimental unit). The clones presented differences in the evaluations of gas exchanges and the A values found were higher than the mean values in the literature, which suggests acclimatization of the clones grown in full sun to light intensity. Moreover, under high light intensity, the values of the Fv/Fm ratio indicated the absence of photoinhibition. There were significant differences for all the parameters of biometrics, except for LW, demonstrating expressive variability for the production of fruits and seeds. The clones presented a high yield of dried almond (1200 to 2900 kg ha -1 ) and the differences among clones in the contents of nutrients for the different compartments were expected, due to the variation of productivity among the materials. Adequate sufficiency ranges for each clone represent a first approach in conditions of cultivation in full sun in Brazil. The nutrient exportation by the shell was high, presenting potential for use as an organic fertilizer when returned to the culture. As for the exportation of some nutrients by the fruit, it reinforced the importance of nutritional replacement via fertilization, so that the reduction of the soil natural fertility does not occur. Finally, intensive cultivation of cocoa in full sun showed high production potential. Keywords: Theobroma cacao L. Ecophysiology. Plant nutrition. Leaf diagnosis.